Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1128/mcb.4.12.2921
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the mouse dihydrofolate reductase gene proceeds unabated through seven polyadenylation sites and terminates near a region of repeated DNA.

Abstract: We observed equimolar transcription throughout the 35-kilobase mouse dihydrofolate reductase structural gene. Transcription termination occurred within a discrete region (900 base pairs) located 1 kilobase beyond the last of seven functional polyadenylation sites and near a repetitive DNA sequence element. The results imply that a distinct genetic signal may be associated with the process of transcription termination.The 5' ends of mature mRNAs in higher eucaryotes correspond to sites of transcription initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…Previous work has shown that transcription terminates approximately 6 kb from 3' of the dhfr termination codon (12). The data from the UV mapping experiments suggested that all of the transcribed RNA was due to initiation in the same region and that there was no significant transcription initiation within the transcribed DNA.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Previous work has shown that transcription terminates approximately 6 kb from 3' of the dhfr termination codon (12). The data from the UV mapping experiments suggested that all of the transcribed RNA was due to initiation in the same region and that there was no significant transcription initiation within the transcribed DNA.…”
Section: Discussionmentioning
confidence: 65%
“…The work presented here combined with our previous results (12) serve to define the boundaries of the dhfr transcription unit. Hybridization of pulse-labeled RNA to filter-bound DNA showed that there was no transcription on the dhfr strand further than 1 kb 5' of the dhfr ATG, and the level of hybridization to the probe mDRT10 suggested that transcription initiated within several hundred nucleotides of the ATG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the majority of eukaryotic genes studied to date, transcription appears to terminate in large regions of DNA, which may span hundreds of nucleotides (Hofer & Darnell, 1981 ;LeMeur et al, 1984;Hagenbuchle et al, 1984;Frayne et al, 1984;Amara et al, 1984). A specific transcription terminator, with homology to a yeast termination signal, has been mapped in the human gastrin gene Baek et al, 1986).…”
Section: Introductionmentioning
confidence: 99%